La lucha por el algodon en la tierras tropicales de Piura. La comunidad indigena de Catacaos y su incorporacion sub - Espinoza Claudio, Cesar (2005)
In this essay historical-anthropological bibliography on the rural society of Catacaos is reviewed to locate the importance of this social group in the socio political history of the north coast. Next the autor examines the strutural factors of the Word of the yunga comunal peasants (land, wáter, work) and their answers to the challenges of the viceregal colonial market. Finally, he examines the ideas and the Project of economic progress of a enlightened Biscayan, Don Joaquin of Helguero y Gorgoya, to overcome the eycle of economic stagnation of the Piuran economy and its visión of the indigenous peasant society in the productive sphere to achieve this plan of economic autonomy at the beginning of the XIX century.